2022
DOI: 10.1177/17562872221096377
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of biparametric MRI (bpMRI) implementation on screening, detection, and the overall accuracy for prostate cancer

Abstract: Prostate cancer is the most common malignancy in American men following skin cancer, with approximately one in eight men being diagnosed during their lifetime. Over the past several decades, the treatment of prostate cancer has evolved rapidly, so too has screening. Since the mid-2010s, magnetic resonance imaging (MRI)–guided biopsies or ‘targeted biopsies’ has been a rapidly growing topic of clinical research within the field of urologic oncology. The aim of this publication is to provide a review of biparame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 55 publications
(92 reference statements)
0
9
0
Order By: Relevance
“…The PI-RADS v2.1 emphasizes that although DCE imaging is essential, its role in the determination of the PI-RADS category is secondary to that of T2-WI and DWI (20). Previous studies have shown that in those patients with PSA levels of 4-10 ng/mL, biparametric MRI (bpMRI) achieved better performance than conventional MRI and mpMRI with higher specificity in detecting PCa and reduced unnecessary biopsies (21)(22)(23). Accordingly, this study aimed to investigate the effectiveness of radiomic features extracted from bpMRI in the identification of PCa and to develop and validate a radiomic nomogram for PCa diagnosis in a subgroup of patients with PI-RADS ≤3 lesions and PSA serum levels of 4-10 ng/mL, providing a practical tool for accurate diagnosis and personalized treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The PI-RADS v2.1 emphasizes that although DCE imaging is essential, its role in the determination of the PI-RADS category is secondary to that of T2-WI and DWI (20). Previous studies have shown that in those patients with PSA levels of 4-10 ng/mL, biparametric MRI (bpMRI) achieved better performance than conventional MRI and mpMRI with higher specificity in detecting PCa and reduced unnecessary biopsies (21)(22)(23). Accordingly, this study aimed to investigate the effectiveness of radiomic features extracted from bpMRI in the identification of PCa and to develop and validate a radiomic nomogram for PCa diagnosis in a subgroup of patients with PI-RADS ≤3 lesions and PSA serum levels of 4-10 ng/mL, providing a practical tool for accurate diagnosis and personalized treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The most serious of these are nausea, vomiting, dizziness, headache, seizure, pulmonary edema, and anaphylaxis [ 64 ], reactions that, while rare, can put the patients in real danger, given that the majority of patients have associated pathological conditions due to PCa and its treatment, other comorbidities, and age. The presence of end-stage renal disease, as well as acute kidney injury, chronic kidney disease, and dialysis, is another issue related to contrast agents [ 65 , 66 ]. The majority of the concerns raised in studies regarding gadolinium-based contrast agents (GBCA) are related to nephrogenic systemic fibrosis [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…As bpMRI does not require the acquisition of contrast agents, it is less expensive than mpMRI. In countries such as the United States of America, the costs vary depending on the healthcare services provided, whereas in Korea, for example, bpMRI costs half as much as mpMRI [ 65 ].These recommendations and suggestions emphasize that the importance of using bpMRI instead of mpMRI whenever possible.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, early detection strategies and improved management approaches are crucial for reducing mortality rates associated with PCa. MRI with T2-weighted and diffusion-weighted sequences is an effective diagnostic tool used in PCa management 8 11 . Accelerating imaging through advanced reconstruction techniques applied to under-sampled data holds the potential to enhance cost-effectiveness in prostate MRI workflows, while automated triage systems can contribute to increased efficiency and broader accessibility of prostate MRI.…”
Section: Background and Summarymentioning
confidence: 99%